Social Support and Externalizing Symptoms in Children from Alcoholic Families - Grzegorzewska, Iwona; Cierpiałkowska, Lidia (Department of Psychology, University of Wrocław, 2014)
This study examines whether social support perceived from different sources can significantly predict behavioral problems in children from alcoholic families. Participants are composed of 540 children in three age groups. We use the Child and Adolescent Social Support Scale and Youth Self Report/YSR 11-18. Our finding was that children of alcoholics have a greater risk of externalizing symptoms in comparison to children of non-alcoholics. Social support significantly predicts behaviour problems in the different life periods. In alcoholic families it was observed that mother, teacher and peer support negatively correlated with externalizing problems in the different developmental periods. Regression Analysis showed that the important predictors for externalizing such problems are low levels of support from teachers (in middle childhood and late adolescence), peers (in middle childhood) and mothers (in early adolescence). Our concluding remark is that social support perceived by children of alcoholics differs from the support perceived by children from control groups. This is important for prevention and therapy.
Keywords: social support sources; behavior problems; children of alcoholics